Eccentricity based topological invariants of triangulane dendrimers - Zobair, Mian Muhammad; Malik, Mehar Ali; Shaker, Hani; Rehman, Noor (Utilitas Mathematica, 2018)
In chemical graph theory, numerical parameters which characterizes the molecular topology and structure of a graph are defined as topological indices. In QSAR/QSPR different theoretical properties of chemical compounds as well as molecular topological indices such as eccentric connectivity index (ECI), modified eccentric connectivity (MECI), total eccentricity and many more are used to predict the bioactivity of chemical compounds. Because of the artificially manufactured architecture dendrimers fascinated the researchers in the development of drug carriers, gene delivery and different biomedical activities. In this paper, we compute eccentric-connectivity index, modified eccentric-connectivity, total- eccentricity, eccentricity-based Zagreb indices and general sum- connectivity index of triangulane and subdivided graphs of triangulane. We derive the analytical closed formulae for this class of dendrimer. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.